Cost Variation Within Spinal Fusion Payment Groups. Issue 22 (15th November 2016) - Wright, David J.; Mukamel, Dana B.; Greenfield, Sheldon; Bederman, S. Samuel
Abstract : Study Design: Retrospective, large administrative database. Objective: To investigate cost variation within current spinal fusion diagnosis-related groups (DRGs). Summary of Background Data: Medicare reimbursement to hospitals for spinal fusion surgery is provided as a fixed payment for each admission based on DRG. This assumes that patients can be grouped into homogenous units of resource use such that a single payment will cover the costs of hospitalization for most patients within a given DRG. However, major differences in costs exist for different methods of spinal fusion surgery. A previous study in total joint arthroplasty (TJA) showed that variation within DRGs can lead to differences between hospital costs and Medicare reimbursement, resulting in predictable financial losses to hospitals and hindering access to care for some patients. No study to our knowledge has investigated cost variation within current spinal fusion DRGs. Methods: Direct hospital costs were obtained from the 2011 Nationwide Inpatient Sample (NIS) for patients in spinal fusion DRGs 453–460 and TJA DRGs 466–470. Our primary outcome was the coefficient of variation (CV), defined as the ratio of the standard deviation (SD) to the mean (CV = SD/mean × 100), for all costs within a given DRG. CVs were compared to an established TJA benchmark for within-DRG cost variation. Results: CVs for costs within spinal fusion DRGs ranged from 44.16 to 52.6 and were significantly higher than the CV of 38.2 found in the TJA benchmark group ( P  < 0.0001). Conclusion: As in TJA, the cost variation observed within spinal fusion DRGs in this study may be leading to differences between costs and reimbursement that places undue financial burden on some hospitals and potentially compromises access to care for some patients. Future studies should seek to identify drivers of cost variation to determine whether changes can be made to further homogenize current payment groups and ensure equal access for all patients. Level of Evidence: 3 Abstract : Supplemental Digital Content is available in the text